Dominance of Global Visual Properties at Birth. - Cassia, Viola Macchi; Simion, Francesca; Milani, Idanna (Journal of Experimental Psychology. General, 2002)
Six experiments are reported that were aimed at demonstrating the presence in newborns of a perceptual dominance of global over local visual information in hierarchical patterns, similar to that observed in adults (D. Navon, 1977, 1981). The first four experiments showed that, even though both levels of visual information were detectable by the newborn (Experiments 1A and 1B), global cues enjoyed some advantage over local cues (Experiments 2 and 3). Experiments 4A and 4B demonstrated that the global bias was strictly dependent on the low spatial frequency content of the stimuli and vanished after selective removal of low spatial frequencies. The results are interpreted as suggesting parallels between newborns' visual processing and processing later in development. Reprinted by permission of the publisher.